Usage of unpublished paediatric data. Issue 1 (5th November 2015) - Saint-Raymond, Agnès; Pelle, Benjamin; Zaccaria, Cosimo; Sennwitz, Matthias; Branch, Sarah
Abstract : The European Paediatric Regulation (EC No 1901/2006) has three main objectives: increasing the number of appropriate medicines for children, increasing information on these medicines and stimulating high-quality ethical research with children. To contribute to the information, pharmaceutical companies were required under article 45 of the Regulation to submit existing paediatric studies to regulatory authorities for review and update of the product information. Nearly, 19 000 study reports have been identified for a thousand active substances. The data are being assessed by member states' competent authorities in collaboration with European Medicines Agency (EMA). After 7 years, 262 active substances have been assessed, all of the 62 centrally approved and nearly 200 nationally approved medicines. The review so far has led to 16 new paediatric indications, of importance in addressing previously unmet needs, in particular, in younger age groups. The information is being made publicly available in an EMA database accessible directly or through the public face of the European Clinical Trials Register. This will increase awareness of existing data that are useful to researchers and other healthcare professionals, and contribute to avoiding unnecessary duplication of paediatric trials.